The Real Walmart. (September 2015) - Morillo, Juan; McNally, Callie; Block, Walter E.
Abstract The Walmart Company is one of the favorite punching bags of market critics. They accuse this firm of underpaying employees, dealing unfairly with customers, exploiting suppliers, and bankrupting small competitors. Various political jurisdictions have banned this firm from their environs, either implicitly or explicitly. The present article offers a more nuanced position on the behemoth from Arkansas. Although it has some flaws, there is an overwhelming case to be made in its behalf as an employer, competitor, purchaser, benefactor of customers.